Aesthetic Periodontal Surgical Approach for Preparing Direct Veneer: A Case Report - Yudin, Muhammad; Thahir, Hasanuddin; R Nahusona, Donald; Rezdy Asalui, Trisantoso; Eka Satya, Dian (KnE Medicine, 2022)
Background: Gingival enlargement is caused by cervical dental plaque accumulation and worsened by cervical caries. Gingivectomy, gingivoplasty and ablation procedures are the surgical techniques used to improve the aesthetics and physiologic functions of hyperpigmented fibrotic gingival tissues. Objective: To provide aesthetic satisfaction to patients treated for direct veneer restoration. Case Report: A 19-year-old male patient came to RSGM UNHAS with a chief complaint of caries on the right maxillary incisors, extending from labial to cervical sections, showing gingival enlargement of the teeth. Intraoral examination revealed caries and gingival enlargement with uneven gingival color. Gingivectomy, gingivoplasty and ablation were performed on the patient using a scalpel, then direct veneer restorations were performed. Results: The two-week control period showed reduction in gingival enlargement and uniform gingival color. Conclusion: A periodontal aesthetic surgy in the form of gingivectomy, gingivoplasty, and ablation maximizes esthetic results. Keywords: ablation, direct veneer, gingivectomy, gingivoplasty